MAIN PROBLEMS OF TRANSLATION. - Shomurodova Dildora Anvarovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. This article explores the fundamental problems encountered in the process of translation. It highlights the key linguistic and cultural challenges that translators face, including lexical, grammatical, stylistic, cultural, and pragmatic issues. Through relevant examples and theoretical insights, the paper emphasizes the importance of context, cultural awareness, and communicative intent in achieving accurate and effective translation. The discussion aims to contribute to a deeper understanding of translation as a complex act of cross-cultural communication rather than a simple linguistic operation.